Historical narrative and wisdom. Towards preaching Esther "for such a time as this" - Arie C. Leder (Acta Theologica)
This article considers the problem of preaching OT historical narrative from the point of view of the depiction of God’s participation in the drama. It suggests that historical narrative in general depicts a God who reveals himself infrequently, that his presence is normally veiled, and that the reader often has more information about God than the characters in the narrative. The discussion then focuses on Esther where God is resolutely veiled, even from the reader, were it not for the inter-textual references which the competent reader of OT historical narrative will discern. The article suggests that biblical wisdom literature, which discerns God’s veiled presence without respect to acts in history, can be employed to profitably preach Esther in a world where God is present, but readers experience him as veiled. The article ends with suggestions for a series of sermons on Esther.